Removal of phenol from aqueous solutions by adsorption onto Mn-Ce-K solids - D'alessandro, Oriana (2014)
Mn-Ce solids were used for the adsorption of phenol from aqueous solution at 25 and 50 C. The samples were prepared with a Mn-Ce molar ratio Between 0 and 100 % by the alkaline co-precipitation method (KOH). Structural studies showed the formation of cryptomelane, Mn2O3, Mn5O8, Mn3O4 and CeO2. The formation of different phases is a function of the Ce concentration. The adsorption isotherms of phenol were determined and modelled with Langmuir and Freundlich equations. Sample 7/3 had a high adsorption capacity. Thermodynamic parameters, in flat and vertical position of phenol, were calculated. These parameters indicated that the adsorption of phenol onto Mn-Ce was spontaneous and exothermic. The DRIFTS study detected of both phenol and phenolate species adsorbed on the surface and the aromatic ring of phenol is parallel to the surface. The interaction between Mn and Ce enhanced the reducibility of the oxides and activated oxygen, which is favorable for the adsorption process.